1999
DOI: 10.1037/0022-3514.77.6.1296
|View full text |Cite
|
Sign up to set email alerts
|

Linguistic styles: Language use as an individual difference.

Abstract: Can language use reflect personality style? Studies examined the reliability, factor structure, and validity of written language using a word-based, computerized text analysis program. Daily diaries from 15 substance abuse inpatients, daily writing assignments from 35 students, and journal abstracts from 40 social psychologists demonstrated good internal consistency for over 36 language dimensions. Analyses of the best 15 language dimensions from essays by 838 students yielded 4 factors that replicated across … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

59
1,302
10
30

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 1,454 publications
(1,454 citation statements)
references
References 53 publications
59
1,302
10
30
Order By: Relevance
“…Previous studies have documented the relations of neuroticism with perfectionism (Hill, McIntire, & Bacharach, 1997), greater engagement in lower visibility behaviors (e.g., negative inner thought processing), and self-evaluation (Funder & Dobroth, 1987). These findings also confirm previous research that those high on neuroticism tend to use more negative emotion words across contexts (Pennebaker and King, 1999).…”
Section: Question #3: How Are the Self-concept Dimensions Related To supporting
confidence: 81%
See 2 more Smart Citations
“…Previous studies have documented the relations of neuroticism with perfectionism (Hill, McIntire, & Bacharach, 1997), greater engagement in lower visibility behaviors (e.g., negative inner thought processing), and self-evaluation (Funder & Dobroth, 1987). These findings also confirm previous research that those high on neuroticism tend to use more negative emotion words across contexts (Pennebaker and King, 1999).…”
Section: Question #3: How Are the Self-concept Dimensions Related To supporting
confidence: 81%
“…It has previously been found that people high on conscientiousness tend to use more positive emotion words (e.g., Pennebaker & King, 1999). Indeed, in this study, we found that conscientiousness had a positive correlation with Maturity (r = .13, p <.001).…”
Section: Question #3: How Are the Self-concept Dimensions Related To supporting
confidence: 70%
See 1 more Smart Citation
“…For instance, AI has been scored in U.S. presidents' inaugural speeches (e.g., Winter, 1991Winter, , 2001, letters of CEOs to the stockholders of their companies (Diaz, 1982, in McClelland, 1987, and, with a slightly extended scoring criterion, in the diaries of substance abuse patients and the journal abstracts of social scientists (Pennebaker & King, 1999). Thus, the verbal material that people generate in their private and professional lives may provide clues to how they deal with stressful challenges; whether they are more likely to recruit RH functions, LH functions, or both in equal measure.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Past research suggests that these different orientations are apparent in narratives. In a study of written narratives, introversion was found to be associated with a tendency to make distinctions through the use of exclusive words such as "but" and "except," and tentative words such as "perhaps" and "maybe," while extraversion was associated with a higher frequency of inclusive words, such as "and" and "with" (Pennebaker & King, 1999). In a study of TAT stories, extraverts more often imported other characters into stories about a solitary figure than did introverts (Shapiro & Alexander, 1975).…”
mentioning
confidence: 99%